Object Theatre and the indian context (Móin-Móin - Revista de Estudos sobre Teatro de Formas Animadas, 2024)
This article is a series of reflections generated through research and practice of an Indian Object Theatre company from 2011-2023. It reflects from the standpoint of the Indian context while looking at the history, development and practices in other parts of the world.
Keywords: teatro de objetos; contexto indiano; processos criativos; Tram Arts Trust